The little blue bridge - Maier, Brenda (Brenda J.) (Scholastic Press, an imprint of Scholastic Inc., 2021)
Loosely adapted from The Three Billy Goats Gruff, Ruby and her brothers want to cross a bridge to pick blueberries, but it is guarded by the bully Santiago--the boys manage to trick him, but clever Ruby takes a different tack, builds her own bridge, and turns Santiago into an ally and friend.